Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Helm Merek GM Pada Mahasiswa/i Sekolah Tinggi Ilmu Ekonomi Haji Agus Salim Bukittinggi - Hariman Syaleh; Rohimah Nur Nasution (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
This research is motivated by many types and brands of helmets offered to consumers in the market. So that each helmet company must create a strategy to maintain and achieve a higher market share. The problem in this study is "How is the influence of price, quality and promotion of the decision to purchase GM brand helmets for STIE HAS Bukittinggi students. The data used are primary and secondary data. The research data was obtained through questionnaires to 68 respondents. The variables used were dependent variables, namely purchasing decision (Y) and independent variables namely price (X1), and promotion (X2). The method of analysis used by the writer in this research is multiple linear regression analysis. The results of multiple linear regression analysis obtained the following equation: Y = 15,070 + 0,222 X1 + 0.782 X2 obtained that prices and promotions have a positive effect on purchasing decisions. The results of the t test and f test are partially and simultaneously have a significant effect on purchasing decisions.